Individual determinants of women on boards and corporate social performance: a study on Malaysian public listed companies / Amirah Aqilah Mohd Zakaria - Mohd Zakaria, Amirah Aqilah (2019)
This study examines the influence of number of women, qualification of women, age of women, and tenure of women on corporate boards towards firm corporate social performance of more than 300 Malaysian public companies listed on Bursa Malaysia. Data for this study had been collected from the annual reports that were available on Bursa Malaysia's database for year 2018. This study had utilized a purposive sampling method where a total of 338 public listed companies had been chosen as the sample. The result of this study indicated that the firm corporate social performance was influenced by a few women characteristics on corporate boards. The result reveals that there is a significant and positive association between number of women on corporate boards and firm corporate social performance. On the other hand, the findings also revealed that the qualification of women, age of women, and tenure of women on corporate boards to have some negative relationships with the firm corporate social performance. Of all the determinants or women characteristics, this study found that the number of women on corporate boards is the strongest individual determinant influencing firm corporate social performance. In terms of contribution, this study proposed some contributions to the body of knowledge and highlighted some practical solution. Additionally, this study has provided the evidence on the effects of corporate governance reforms in terms of encouraging participation of women on the board of directors, which suggests that women on corporate boards can positively influence the firm corporate social performance.